2004
DOI: 10.17221/5706-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Fractionized milk composition in dairy cows with subclinical mastitis

Abstract: ABSTRACT:Mastitis is the inflammatory reaction of the udder to invading pathogens. One of the most apparent reactions is the increased influx of immunoreactive cells from blood into milk inducing a dramatic increase of milk somatic cell counts (SCC). We have investigated (i) the relationship between log SCC/ml in infected quarters being >6 (n = 8, group I) or varying between 5.4 and 6 (n = 8, group II) and concentration of dry ma�er (DM), fat, protein, lactose, insulin-like growth factor (IGF)-1, insulin, prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

21
81
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 19 publications
(30 reference statements)
21
81
0
5
Order By: Relevance
“…This increase has been reported in many studies (Ontsouka et al, 2003;Bruckmaier et al, 2004;Sarikaya et al, 2005;Tan in et al, 2007). It is likely that the fat droplets, which are delimited by lipoprotein membranes, are held back by capillary forces in the alveoli and through adhesive forces on the udder epithelium during the process of milking.…”
supporting
confidence: 60%
See 3 more Smart Citations
“…This increase has been reported in many studies (Ontsouka et al, 2003;Bruckmaier et al, 2004;Sarikaya et al, 2005;Tan in et al, 2007). It is likely that the fat droplets, which are delimited by lipoprotein membranes, are held back by capillary forces in the alveoli and through adhesive forces on the udder epithelium during the process of milking.…”
supporting
confidence: 60%
“…Other studies found a similar lactose and protein content (Ontsouka et al, 2003;Bruckmaier et al, 2004, Sarikaya et al, 2005. The reasons for the decrease over the course of milking of both protein and lactose are unclear, but it is conceivable that contents of water-soluble milk constituents decrease when fat content rises towards the end of milking.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…In previous studies by Bruckmaier et al (2004) the osmolality of raw milk was found to lie between 284 and 295 mOsmoles . In similar investigations, the osmolality of pasteurized milk was found to be in the range 274-281.5 (mean of 277.8 mOsmoles kg…”
Section: Discussionmentioning
confidence: 90%